Polymorphism and inconsistencies in the taxonomy of Diplodinium anisacanthum da Cunha, 1914 (Ciliophora, Entodiniomorphida, Ophryoscolecidae) and taxonomic notes on the genus Diplodinium Schuberg, 1888 - Cedrola, Franciane; Dias, Roberto Júnio Pedroso; Martinele, Isabel; D’agosto, Marta (Zootaxa, 2017)
The genus Diplodinium includes 31 species of ophryoscolecid ciliates with two retractable ciliary zones in the anterior end of the body, with no skeletal plates, inclined macronucleus and two contractile vacuoles. They have a broad geographical distribution and low host specificity. The genus has several taxonomic inconsistencies, mainly due to polymorphism of most species. Diplodinium anisacanthum is a case of taxonomic inconsistency in the genus. It presents polymorphism in posterior end of the body, so it is considered a polymorphic species or seven distinct species. This study presents the morphological characterization of six D. anisacanthum morphotypes based on general morphology, morphometric analysis and oral infraciliature characterization and taxonomic notes on the genus Diplodinium. The morphological and morphometric characterization of D. anisacanthum showed great similiarities among morphotypes suggesting that these ciliates constitute a single species with polymorphisms. A brief review conducted highlights the inconsistencies in the taxonomy of the genus Diplodinium and demonstrates the need for recent studies with representatives of the genus. There is no information on how polymorphism of Diplodinium anisacanthum morphotypes correlates to molecular data, since there are only two sequences of this species available in the GenBank database.